Population parameters of sawtooth barracuda Sphyraena putnamae (Jordan and Seale, 1905) exploited along western Bay of Bengal - Ghosh, Shubhadeep; Satishkumar, M.; Manas, H. M.; Rohit, Prathibha; Abdussamad, E. M.; Gopalakrishnan, A. (Indian Journal of Fisheries, 2021)
Population parameters have been studied in nine of the 21 species of barracudas reported globally. Along the Bay of Bengal, Sphyraena putnamae (Jordan and Seale, 1905) forms a significant fishery; however, no information exists globally with respect to its growth, mortality and exploitation. This maiden study details the population dynamics analysed from samples collected from trawlnetters, gillnetters and hooks and lines along the western Bay of Bengal during January 2017 to December 2019. The mean fork length in the catch was 50.8 cm with the largest individual measuring 108.0 cm, the highest ever length recorded for the species. von Bertalanffy growth equation derived is Lt = 113.87 [1 - e -0.23 (t + 0.0636)]. The fishery was dominated by 1-4 year old age classes and lifespan estimated was 12.98 years. Year-round recruitment with the major peak producing 60.87% of the annual recruits was observed from February to June. Natural, fishing and total mortalities were 0.46, 0.25 and 0.71 per year, respectively. Exploitation rate (E) estimated was 0.35 with the exploitation ratio (U) being 0.18. Though the current status indicates that the stock is underexploited, it is however prudent to adopt a precautionary approach, considering the small size as well as age of exploitation, through adoption of measures such as increase in mesh size of trawlnetters and spatio-temporal fishing restrictions in nearshore nursery waters. Keywords: Bay of Bengal, Exploitation, Growth, Mortality, Sawtooth barracuda, Sphyraena barracuda